Logic’s visual identity: Contribution to reputation management in the logistics outsourcing sector - Lopes de Castro, Isabel (Convergences - Journal of Research and Arts Education, 2021)
The visual identity seems to have strategic relevance for companies or organizations as it enables the communication of organizational identity as well as positioning and can be assumed as the unifying element of image with audiences, allowing differentiation from others. In January 2006, Logic had ambitious goals to grow its turnover for the following years and needed to gain a reputation in the logistics outsourcing setor. Within the scope of this study, non-interventionist methodologies and an exploratory case study were adopted. The case study consisted of an active research component, with the development of a design project. This article presents the process that led to the creation of the Logic´s visual identity.